Association of Plasma Neutrophil Elastase and Interleukin 1 Beta Levels with Metabolic Syndrome in Obese Premenopausal Women - Moushira Zaki (Journal of Global Pharma Technology, 2019)
Introduction: Metabolic syndrome (MS) is the state of chronic low grade inflammation. Plasma neutrophil elastase (NE) might be a critical marker associated with several choric diseases. However, relation of NE, interleukin 1 beta (IL-1β) and MS and its complications in Egyptian obese women has not been yet investigated. The aim of this study is to determine the relationship between levels of NE, IL-1β with MS and metabolic components in obese premenopausal women. Methods: This cross-sectional study was conducted on 150 obese women with MS and 150 non obese healthy women matched in age. Inflammatory markers including NE and IL-1β were measured by ELISA. Blood pressure (BP), blood glucose, lipid profile and insulin sensitivity were studied. Insulin resistance was assessed by the homeostasis assessment model (HOMAIR) and insulin sensitivity by quantitative insulin sensitivity. Body fat % was assessed by Body composition analyzer. Results: MS patients showed significant higher levels of NE, IL-1β, fasting insulin, glucose and HOMA-IR and markers of serum lipid parameters (increase of triglycerides, low density lipoprotein, total cholesterol and decrease of high density lipoprotein), elevated levels of SBP and DBP than non obese controls. In addition, significant positive correlations were observed between NE and metabolic components of MS. Partial correlations revealed significant positive relation between NE, IL-1β and HOMAIR, body fat % in obese MS cases after adjustment of BMI and age. Conclusion: NE and IL-1β and body fat % are elevated in obese women with MS, suggesting their critical role in MS complications in obese Egyptian women and emphasized that these biomarkers might be used as good indicators for severity of the disease.Keywords: Metabolic syndrome, Interleukin 1 beta, Neutrophil elastase, Insulin sensitivity.